Conversational Intelligence for All: Speech Recognition Systems for Inclusive Digital Access (London Journal of Engineering Research, 2025)
Digital service accessibility confronts enduring challenges in multilingual societies, where technological and linguistic barriers limit participation for numerous population segments. Voice-based interfaces operating through telephone systems present valuable pathways to narrow these divides, facilitating interaction without literacy prerequisites or technical proficiency. Telephone-based speech recognition faces distinctive technical obstacles, including limited bandwidth, ambient noise interference, and natural conversational patterns substantially different from laboratory speech inputs. Modern algorithmic techniques, especially those employing probabilistic modeling frameworks, show remarkable capacity to function within these demanding audio environments while handling regional accents and language variations. Practical implementations across transit networks, administrative service systems, and learning platforms demonstrate how these technologies establish vital access points for traditionally underserved communities. Such systems support transportation schedule inquiries, social program registration, and educational material engagement via conventional telephone infrastructure instead of demanding broadband connections or advanced mobile devices. Widespread implementation requires thoughtful attention to information security protocols, recognition fairness across accent variations, and strategic language selection to prevent perpetuating societal imbalances. This contribution outlines system architectures, deployment methodologies, and performance assessment frameworks for developing genuinely inclusive conversational technologies that broaden digital participation across communication and technological boundaries.
Keywords: Speech Recognition Systems; Inclusive Digital Access; Multilingual Technologies; Telephone-based Interfaces; Digital Accessibility